2014
DOI: 10.5572/kosae.2014.30.2.119
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Urban Heat Island in Seoul using Local Analysis System

Abstract: A very high resolution weather analysis system (VHRAS) of 50 m horizontal resolution is established based on LAPS. VHRAS utilizes the 3 hourly forecast data of the Unified Model (UM) of the Korea Meteorological Administration (KMA) with the horizontal resolution of 12 km as initial guess fields. The analysis system ingests the automatic weather station (AWS) data as input observations. The analysis system operates every hour for Seoul, Korea region in real time basis. It takes less than 10 minutes for one anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Hajat et al also showed a greater heat effect on mortality among those living in urban areas, while cold effects were greater in some rural areas [ 20 ]. The heat effect in urban areas is probably due to the heat-island effect, whereby greater heat retention occurs in more heavily built-up areas of large cities, including in South Korea [ 59 ]. Our study did not show a higher risk in the rural population in cold weather, probably because of reduced daily activities in the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…Hajat et al also showed a greater heat effect on mortality among those living in urban areas, while cold effects were greater in some rural areas [ 20 ]. The heat effect in urban areas is probably due to the heat-island effect, whereby greater heat retention occurs in more heavily built-up areas of large cities, including in South Korea [ 59 ]. Our study did not show a higher risk in the rural population in cold weather, probably because of reduced daily activities in the winter season.…”
Section: Discussionmentioning
confidence: 99%